Predictive value of geriatric nutritional risk index in cardiac and cerebrovascular events after endovascular aortic aneurysm repair - Zou, YuPei; Wang, Jiarong; Zhao, Jichun; Ma, Yukui; Huang, Bin; Yuan, Ding; Liu, Yang; Han, Maonan; Gan, Huatian; Yang, Yi (Frontiers in Cardiovascular Medicine, 2024)
Objective: To evaluate the effect of malnutrition assessed by the Geriatric Nutritional Risk Index (GNRI) on major adverse cardiac and cerebrovascular events (MACCE) in the elderly patients after endovascular aortic aneurysm repair (EVAR). 95% CI -3.88, -0.05, p = 0.0454). GNRI status was associated with a significantly increased risk of long-term mortality after EVAR (Medium GNRI, unadjusted ORHR 0.40, 95%CI 0.23-0.70,p=0.0014; adjusted ORHR 0.47, 95%CI 0.26-0.84, p=0.0107; high GNRI, 0.27 95%CI 0.14-0.55; p=0.0003; adjusted ORHR 0.32 95%CI 0.15-0.68,p= 0.0029). Both medium and high GNRI values were linked to significantly reduced risks of MACCE compared to low GNRI score patients (Medium GNRI, unadjusted ORHR 0.34, 95%CI 0.13-0.88,p=0.00265; adjusted ORHR 0.37, 95%CI 0.14-0.96, p=0.0408; High GNRI, 0.26 95%CI 0.09-0.78; p=0.0168; adjusted ORHR 0.21 95%CI 0.06 -0.73,p= 0.0029, Table 3). Compared with the RCRI and mFI, the GNRI had better discrimination in predicting long-term MACCE. An area under the curve (AUC) for GNRI mFI, and RCRI is 0.707, 0.614 and 0.588, respectively. (Z statistic, GNRI vs mFI, p=0.0475; GNRI vs RCRI, p=0.0017).Malnutrition assessed by the GNRI may serve as a useful predictor of long-term MACCE in elderly patients after EVAR, with preferable discrimination abilities compared with both RCRI and mFI.